Non-Renewable Resources and Disequilibrium Macrodynamics. - Marks, Robert (Routledge Library Editions: Environmental and Natural Resource Economics, 2017)
This study, first published in 1979, continues by examining the question of whether a competitive economy can efficiently allocate a stock of non-renewable natural resources through time. Long-run analyses of competitive economies with such resources have concluded that, without perfect foresight or a complete set of future markets extending infinitely far into the future, there is no economic mechanism to guarantee that the initial price is set so that the economy converges to the socially desirable path of balanced growth. This title will be of interest to students of environmental and natural resource economics.